Action levels for indoor radon: different risks for the same lung carcinogen?. Issue 5 (9th November 2017) - Ruano-Ravina, Alberto; Kelsey, Karl T.; Fernández-Villar, Alberto; Barros-Dios, Juan M.
Assessment of the various risk factors for lung cancer has found that indoor radon exposure is the primary risk factor for lung cancer in never-smokers and the second ranked risk factor in ever-smokers [1, 2], following tobacco. Radon exposure is responsible for approximately half of the total ionising radiation that the average human being receives in a lifetime (followed in magnitude by medical radiation) and is the largest source of natural ionising radiation [3]. Radon is a colourless, odourless and tasteless gas that comes from the bedrock of the Earth's crust. Radon 222 is the most dangerous and the most common form of radon, from an epidemiological point of view, as 80% of all radon is radon 222. Indoor radon is usually measured in becquerels per cubic metre, and 1 becquerel per cubic metre is equivalent to one nuclear disintegration per second in such a volume. One nuclear disintegration releases one alpha particle. Radon is the second most important risk factor for lung cancer but recommended exposure differs in many countries http://ow.ly/VZ8y30fDdYz